The Influence Of Marketing, Product And Brand Communications On Purchasing Decisions In The Digital Era - Pranawukir, Iswahyu (International Journal of Artificial Intelligence Research, 2024)
The purpose of this research is to determine the influence of marketingcommunications, products and brands on purchasing decisions in theDigital Era. The method in this research is survey research with aquantitative approach, assessment based on numbers using statisticalcalculations, using simple random sampling techniques and datacollection techniques in this research using library research, fieldresearch, observation and questionnaires. This research used a sample of100 potential consumers who had experience purchasing products orservices in the digital era. Data was processed using SPSS version 25.The research results show that the Marketing Communication variable(X1) partially has a significant positive effect on Purchasing Decisions(Y) with a t-count value > t-table (2.926 > 1.988) with a value (sig) of0.004 < 0.05. The Product variable (X2) partially has a significantpositive effect on Purchasing Decisions (Y) with a t-count > t-tablevalue (2.033 > 1.985) with a value (sig) 0.045 < 0.05, the Brand variable(X3) partially has no effect on Purchasing Decisions (Y) with a t-countvalue > t-table (-1,000 < 1.985) with a value (sig) 0.320 > 0.05 . And thevariables marketing communication (X1), Product (X2) and BrandPerception (X3) simultaneously have a significant positive effect on thePurchasing Decision variable (Y) F-count value > F-table or 8.511 >2.70 and significant < 0.05 (0.000 < 0.05). The coefficient ofdetermination (adjust R Square) is 0.925 or 92.5%, which means thatthe independent variables consisting of marketing communications(X1), products (X2) and brands (X3) can contribute an influence of 21%and the remaining 79%. influenced by other factors